2013
DOI: 10.1371/journal.pcbi.1003203
|View full text |Cite
|
Sign up to set email alerts
|

The Individualized Genetic Barrier Predicts Treatment Response in a Large Cohort of HIV-1 Infected Patients

Abstract: The success of combination antiretroviral therapy is limited by the evolutionary escape dynamics of HIV-1. We used Isotonic Conjunctive Bayesian Networks (I-CBNs), a class of probabilistic graphical models, to describe this process. We employed partial order constraints among viral resistance mutations, which give rise to a limited set of mutational pathways, and we modeled phenotypic drug resistance as monotonically increasing along any escape pathway. Using this model, the individualized genetic barrier (IGB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“… 19 , 20 , 21 The effect of resistance mutations on viral replication fidelity might also protect the protease inhibitor by limiting the development of new mutations to escape drug pressure, thus increasing regimen durability. 22 , 23 Pharmacokinetic considerations might enhance these benefits; NRTIs, such as tenofovir and lamivudine, have long intracellular half-lives that might help to maintain viral suppression when protease inhibitor levels are low (with late or occasional missed doses) and this effect might be independent of predicted activity. This potential effect could explain why we observed that the NRTIs were capable of matching the suppression obtained with raltegravir (a drug with a relatively short intracellular half-life) in combination with a protease inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 , 21 The effect of resistance mutations on viral replication fidelity might also protect the protease inhibitor by limiting the development of new mutations to escape drug pressure, thus increasing regimen durability. 22 , 23 Pharmacokinetic considerations might enhance these benefits; NRTIs, such as tenofovir and lamivudine, have long intracellular half-lives that might help to maintain viral suppression when protease inhibitor levels are low (with late or occasional missed doses) and this effect might be independent of predicted activity. This potential effect could explain why we observed that the NRTIs were capable of matching the suppression obtained with raltegravir (a drug with a relatively short intracellular half-life) in combination with a protease inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a documented subtype B INSTI resistance pathway attributed to differential codon usage at position 140 (17,(21)(22)(23), the role of baseline nucleotide variation on INSTI resistance development has been less systematically investigated. The probabilistic models of resistance evolution that previously quantified the genetic barrier for the historical drug classes require sequence data of various subtypes from treatmentexperienced patients (4)(5)(6), which are limited to date in the context of INSTIs (19,24). Alternatively, the genetic barrier can be estimated by the number and type of required nucleotide substitutions to evolve from a wild-type virus to a resistant mutant (25).…”
mentioning
confidence: 99%
“…In clinical settings, viral fitness is also of great interest. Disease progression, the formation of escape mutants, and ultimately treatment failure depend on viral fitness ( Clavel and Hance 2004 ; Beerenwinkel et al 2013 ).…”
mentioning
confidence: 99%